Ankyrin‐repeat proteins from sponge symbionts modulate amoebal phagocytosis. Issue 6 (26th August 2013) - Nguyen, Mary T. H. D.; Liu, Michael; Thomas, Torsten
Abstract Bacteria–eukaryote symbiosis occurs in all stages of evolution, from simple amoebae to mammals, and from facultative to obligate associations. Sponges are ancient metazoans that form intimate symbiotic interactions with complex communities of bacteria. The basic nutritional requirements of the sponge are in part satisfied by the phagocytosis of bacterial food particles from the surrounding water. How bacterial symbionts, which are permanently associated with the sponge, survive in the presence of phagocytic cells is largely unknown. Here, we present the discovery of a genomic fragment from an uncultured gamma‐proteobacterial sponge symbiont that encodes for four proteins, whose closest known relatives are found in a sponge genome. Through recombinant approaches, we show that these four eukaryotic‐like, ankyrin‐repeat proteins (ARP) when expressed in Eschericha coli can modulate phagocytosis of amoebal cells and lead to accumulation of bacteria in the phagosome. Mechanistically, two ARPs appear to interfere with phagosome development in a similar way to reduced vacuole acidification, by blocking the fusion of the early phagosome with the lysosome and its digestive enzymes. Our results show that ARP from sponge symbionts can function to interfere with phagocytosis, and we postulate that this might be one mechanism by which symbionts can escape digestion in a sponge host.